Polishing pad formed from dual curing agents
By using isocyanate-capped urethane prepolymer and specific curing systems in the polishing layer of the chemical mechanical polishing pad, the problems of polishing defects and insufficient removal rates are solved, achieving more efficient polishing effects and better wafer surfaces quality.
Patent Information
- Application Number
- CN202411007709.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-18
AI Technical Summary
During the chemical mechanical polishing process, polishing defects such as scratches and trembling marks are easily formed, and the removal rate is insufficient.
The polishing layer is adopted that includes a urethane prepolymer with isocyanate blocked urethane prepolymer and a curing system, which includes a sulfur-containing diamine curing agent and a high molecular weight polyol curing agent with a specific number average molecular weight and hydroxyl group. Quantity, and the weight ratio of the sulfur-containing diamine curing agent to the high molecular weight polyol curing agent is within a specific range.
The occurrence of polishing defects is significantly reduced while improving the removal rate, ensuring the flatness and quality of the wafer surface.
Smart Images

Figure BDA0004963415360000091 
Figure BDA0004963415360000101 
Figure BDA0004963415360000102
Abstract
Description
Technical Field
[0001] The present invention relates to a polishing pad that can be used for chemical mechanical polishing. Background Art
[0002] In the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive and dielectric materials are deposited onto and removed from the surface of a semiconductor wafer. Many deposition techniques can be used to deposit thin layers of conductive, semiconductive and dielectric materials. Common deposition techniques in modern wafer processing include physical vapor deposition (PVD) (also referred to as sputtering), chemical vapor deposition (CVD), plasma enhanced chemical vapor deposition (PECVD) and electrochemical plating. Common removal techniques include wet and dry isotropic and anisotropic etching.
[0003] As material layers are deposited and removed in sequence, the top surface of the wafer becomes non-planar. Because subsequent semiconductor processing (e.g., metallization) requires the wafer to have a flat surface, the wafer needs to be planarized. Planarization is used to remove undesirable surface topography and surface defects, such as rough surfaces, agglomerated materials, lattice damage, scratches, and contaminated layers or materials.
[0004] Chemical mechanical planarization, or chemical mechanical polishing (CMP), is a common technique for planarizing or polishing a workpiece such as a semiconductor wafer. In conventional CMP, a wafer carrier or polishing head is mounted on a carrier assembly. The polishing head holds the wafer and positions the wafer to contact the polishing layer of a polishing pad, which is mounted on a workbench or platen within the CMP apparatus. The carrier assembly provides a controllable pressure between the wafer and the polishing pad. At the same time, a polishing medium (e.g., slurry) is dispensed onto the polishing pad and sucked into the gap between the wafer and the polishing layer. In order to perform polishing, the polishing pad and the wafer are typically rotated relative to each other. As the polishing pad rotates under the wafer, the wafer sweeps out a typically annular polishing track or polishing area, in which the surface of the wafer directly faces the polishing layer. The wafer surface is polished and made flat by the chemical and mechanical action of the polishing layer and the polishing medium on the surface.
[0005] Defects such as scratches and chatter marks may be formed in the polished substrate during the polishing process.
[0006] It would be desirable to have a pad that reduces polishing defects while maintaining or improving other important properties such as removal rate. Summary of the invention
[0007] Disclosed herein is a chemical mechanical polishing pad comprising a polishing layer having a polishing surface, wherein the polishing layer comprises a reaction product of an isocyanate-terminated urethane prepolymer and a curing system; the curing system comprises a sulfur-containing diamine curing agent and a high molecular weight polyol curing agent, wherein the high molecular weight polyol curing agent has a number average molecular weight Mn of 2,500 to 100,000; and wherein the high molecular weight polyol curing agent has an average of 3 to 10 hydroxyl groups per molecule; wherein the weight ratio of the high molecular weight polyol curing agent to the sulfur-containing diamine curing agent is in the range of 3:10 to 7:10. DETAILED DESCRIPTION Isocyanate-terminated urethane prepolymers
[0008] The isocyanate-terminated urethane prepolymer used in the formation of the polishing layer of the chemical mechanical polishing pad of the present invention may include a reaction product of ingredients including a polyfunctional isocyanate and a prepolymer polyol.
[0009] The polyfunctional isocyanate may be selected from the group consisting of aliphatic polyfunctional isocyanates, aromatic polyfunctional isocyanates, and mixtures thereof. The polyfunctional isocyanate may be a diisocyanate selected from the group consisting of 2,4 toluene diisocyanate; 2,6 toluene diisocyanate; 2,2' diphenylmethane diisocyanate; 2,4' diphenylmethane diisocyanate; 4,4' diphenylmethane diisocyanate; naphthalene 1,5 diisocyanate; toluidine diisocyanate; p-phenylene diisocyanate; xylylene diisocyanate; isophorone diisocyanate; hexamethylene diisocyanate; 4,4' dicyclohexylmethane diisocyanate; cyclohexane diisocyanate; and mixtures thereof.
[0010] The prepolymer polyol may be selected from the group consisting of diols, polyols, polyol diols, copolymers thereof, and mixtures thereof. The prepolymer polyol may be selected from the group consisting of polyether polyols (e.g., poly(oxytetramethylene) glycol, poly(oxypropylene) glycol, poly(oxyethylene) glycol, poly(oxypropylene)-co-poly(oxyethylene) glycol); polycarbonate polyols; polyester polyols; polycaprolactone polyols; mixtures thereof; and mixtures thereof with one or more low molecular weight polyols selected from the group consisting of ethylene glycol; 1,2 propylene glycol; 1,3 propylene glycol; 1,2 butylene glycol; 1,3 butylene glycol; 2 methyl 1,3 propylene glycol; 1,4 butylene glycol; neopentyl glycol; 1,5 pentanediol; 3 methyl 1,5 pentanediol; 1,6 hexanediol; diethylene glycol; dipropylene glycol; and tripropylene glycol. For example, the prepolymer polyol may be selected from the group consisting of at least one of polytetramethylene ether glycol (PTMEG); polypropylene ether glycol (PPG), polyethylene ether glycol (PEG), and polyethylene ether glycol-co-polypropylene ether glycol (PEG-PPG copolymer); optionally, mixed with at least one low molecular weight polyol selected from the group consisting of ethylene glycol; 1,2 propanediol; 1,3 propanediol; 1,2 butanediol; 1,3 butanediol; 2 methyl 1,3 propanediol; 1,4 butanediol; neopentyl glycol; 1,5 pentanediol; 3 methyl 1,5 pentanediol; 1,6 hexanediol; diethylene glycol; dipropylene glycol; and tripropylene glycol. The prepolymer polyol may be primarily (i.e., ≥ 90 wt%) PTMEG.
[0011] The isocyanate-terminated urethane prepolymer may have an unreacted isocyanate (NCO) concentration of 7 to 11.4, 8 to 10, 8.3 to 9.8, 8.5 to 9.5, 8.6 to 9.3, 8.7 to 9.25, or 8.9 to 9.25 wt % based on the total weight of the isocyanate-terminated urethane prepolymer. Examples of commercially available isocyanate-terminated urethane prepolymers include Prepolymers (available from COIM USA, Inc., such as PET 80A, PET 85A, PET 90A, PET 93A, PET 95A, PET 60D, PET 70D, PET 75D); prepolymers (available from LANXESS Urethane Systems, such as LF 800A, LF 900A, LF 910A, LF 930A, LF 931A, LF 939A, LF 950A, LF 952A, LF 600D, LF 601D, LF 650D, LF 667, LF 700D, LF750D, LF751D, LF752D, LF753D, and L325); Prepolymers (available from Anderson Development Company as 70APLF, 80APLF, 85APLF, 90APLF, 95APLF, 60DPLF, 70APLF, 75APLF).
[0012] The isocyanate-terminated urethane prepolymer may be a low-free isocyanate-terminated urethane prepolymer having a free toluene diisocyanate (TDI) monomer content of less than 0.1 wt %. Curing agent
[0013] The curing agents include sulfur-containing diamine curing agents and high molecular weight polyol curing agents.
[0014] The sulfur-containing diamine curing agent may include a diamine-functional aromatic compound having one or more alkylthio groups pendant from an aromatic ring. For example, the sulfur-containing diamine curing agent may include, consist essentially of, or consist of dialkylthiotoluenediamine, monoalkylthiotoluenediamine, or both, in each case wherein the alkyl group contains 1, 2, or 3 carbon atoms. For example, the sulfur curing agent may include, consist essentially of, or consist of monomethylthiotoluenediamine, dimethylthiotoluenediamine, or a combination thereof. For example, the sulfur curing agent may include 95 to 97 weight percent of dimethylthiotoluenediamine based on the total weight of the sulfur-containing diamine curing agent. For example, the sulfur curing agent may include 2% to 3% of monomethylthiotoluenediamine based on the total weight of the sulfur-containing diamine curing agent. For example, the sulfur-containing diamine curing agent may include 3,5-dimethylthio-2,4-toluenediamine, an isomer of 3,5-dimethylthio-2,4-toluenediamine (eg, 3,5-dimethylthio-2,6-toluenediamine), or a combination thereof.
[0015] The high molecular weight polyol curing agent may have a number average molecular weight Mn of 2,500 to 100,000 g. For example, the high molecular weight polyol curing agent used may have a number average molecular weight Mn of 5,000 to 50,000, 7,500 to 25,000, or 10,000 to 12,000. The number average molecular weight may be determined by gel permeation chromatography using polystyrene as a reference.
[0016] The high molecular weight polyol curing agent may have an average of three to ten, four to eight, five to seven, or six hydroxyl groups per molecule.
[0017] Examples of commercially available high molecular weight polyol curing agents include Polyols, Polyols and Polyols (available from Dow Chemical Company); Specialty Polyols and Flexible polyols (available from Covestro AG); and Polyols (available from BASF).
[0018] The present inventors have discovered that using a sulfur-containing diamine curing agent in combination with a high molecular weight polyol curing agent in forming a polishing pad provides an unexpected reduction in defects during polishing compared to using either of these curing agents alone or compared to a high molecular weight polyol in combination with a non-sulfur-containing curing agent such as 4,4'-methylenebis(2-chloroaniline) (MBOCA). Stoichiometry of reactive groups
[0019] The reactive hydrogen groups (i.e., the sum of amine (NH2) groups and hydroxyl (OH) groups) contained in the curing system components (i.e., the high molecular weight polyol curing agent and the difunctional curing agent) used in forming the polishing layer of the chemical mechanical polishing pad of the present invention divided by the unreacted isocyanate (NCO) groups in the isocyanate-terminated urethane prepolymer (i.e., the stoichiometric ratio) can be from 0.85 to 1.15, to 1.05, or to a maximum of 1.0. Pad structure and construction
[0020] The polishing surface of the polishing layer of the chemical mechanical polishing pad of the present invention is adapted to polish a substrate. For example, the polishing surface can be adapted to polish at least one substrate selected from a magnetic substrate, an optical substrate, and a semiconductor substrate. Preferably, the polishing surface is adapted to polish a semiconductor substrate. For example, the polishing surface can be adapted to polish a silicon oxide (e.g., tetraethyl orthosilicate (TEOS)) surface or a silicon nitride (SiN) surface of a semiconductor substrate.
[0021] The polishing surface may have a macrotexture selected from at least one of holes and grooves. The holes may extend partially from the polishing surface or extend all the way through the thickness of the polishing layer. The grooves may be arranged on the polishing surface so that when the chemical mechanical polishing pad rotates during polishing, at least one groove sweeps across the surface of the substrate being polished. For example, the polishing surface may have a macrotexture comprising at least one groove selected from the group consisting of: curved grooves, straight grooves, and combinations thereof.
[0022] For example, the groove design can be selected from the group consisting of: concentric grooves (which can be circular or spiral), curved grooves, radial grooves, mesh grooves (e.g., arranged as an XY grid on the pad surface), other regular designs (e.g., hexagonal, triangular), tire tread type patterns, irregular designs (e.g., fractal patterns), and combinations thereof. For example, the groove design can be selected from the group consisting of: random grooves, concentric grooves, spiral grooves, radial grooves, mesh grooves, XY grid grooves, hexagonal grooves, triangular grooves, fractal grooves, and combinations thereof. As a specific example, the polishing surface can have a concentric groove pattern or a combination of a concentric groove pattern with radial grooves formed therein. The groove profile can be selected from a rectangle with straight sidewalls, or the groove cross-section can be "V" shaped, "U" shaped, serrated, and combinations thereof.
[0023] The polishing layer of the chemical mechanical polishing pad of the present invention may optionally further include a plurality of microelements. The plurality of microelements may be uniformly dispersed throughout the polishing layer. The plurality of microelements may be selected from trapped bubbles, hollow polymer materials, liquid-filled hollow polymer materials, water-soluble materials, and insoluble phase materials (e.g., mineral oil). The plurality of microelements have a volume average diameter of less than 150 μm (more preferably less than 50 μm; most preferably 10 to 50 μm). The plurality of microelements include polymer microspheres. The microspheres may have a polymer composition comprising, for example, polyacrylonitrile or a polyacrylonitrile copolymer (e.g., from Nouryon). A plurality of microelements are incorporated into the polishing layer to provide a porosity of 0 to 50, 5 to 35, or 10 to 25 volume percent.
[0024] The polishing layer of the chemical mechanical polishing pad of the present invention can be provided in both porous and non-porous (ie, unfilled) configurations. The polishing layer of the chemical mechanical polishing pad of the present invention exhibits a pore size as measured according to ASTM D1622. > 0.6g / cm 3 - For example, 0.7 to 1.2, 0.75 to 1.0 or 0.75 to 0.95 g / cm 3 density.
[0025] The polishing layer of the chemical mechanical polishing pad of the present invention can have a Shore D hardness of 40 to 70, 45 to 55, or 50 to 55 as measured according to ASTM D2240. These hardnesses are measured by stacking four 3.81 cm square samples with a thickness of 80 mils (2.032 mm) to eliminate errors from measuring the support surface using a Hoto Instruments Asker P2Durometer with a D probe.
[0026] The polishing layer of the chemical mechanical polishing pad of the present invention exhibits an elongation at break of 125% to 350%, 140% to 300%, or 150% to 200% as measured according to Test Method A in ASTM D412-98a (Reapproved 2002). The test uses an MTS Criterion C43 tester with an Instron 2712-02 load cell with a maximum load of 1000 Newtons and an Instron pneumatic side-acting grip clamped at approximately 30 psi (207 kPa). The test specimens are based on the dimensions of a standard dumbbell mold C, in U.S. customary units, with a thickness of 80 mils (2.032 mm), and the test temperature is at 23°C + / - 2°C. The specimens are deformed under the grip at 20 inches (50.8 cm) + / - 2 inches / minute (5.08 cm / min). Five replicates are measured for each sample, and the average value is reported.
[0027] The polishing layer of the chemical mechanical polishing pad of the present invention can have a shear modulus (at 30° C.) G'30 of 50 to 300, 75 to 250, or 100 to 200 MPa as measured according to ASTM D5279-13 at a sample size of 20.00 mm x 6.53 mm x 2.02 mm. Using a TA Instruments ARES-G2 Torsional Rheometer and a torsion rectangular sample fixture, the heating rate is set to 3° C. / min, the dynamic torsional displacement is 0.2%, and the frequency is 10.0 rad / s.
[0028] The polishing layer of the chemical mechanical polishing pad of the present invention can have a shear modulus (at 40° C.) G′40 of 45 to 275 MPa as measured according to ASTM D5279-13.
[0029] The polishing layer of the chemical mechanical polishing pad of the present invention can have a shear loss modulus (at 40° C.) G″40 of 3 to 20 MPa as measured according to ASTM D5279-13.
[0030] The polishing layer of the chemical mechanical polishing pad of the present invention can have a G'30 / 90 ratio of from 1.5 or from 2 to 4 as measured according to ASTM D5279-13.
[0031] The polishing layer of the chemical mechanical polishing pad of the present invention can have a toughness of from 20 or from 25 to 80, to 70, to 60, to 50 or to 40 MPa calculated according to the stress-strain curve measured in Test Method A in ASTM D412-98a (Reapproved 2002) as described above.
[0032] The polishing layer of the chemical mechanical polishing pad of the present invention can have a tensile strength of from 10 or from 15 to 35, to 30 or to 25 MPa as measured according to Test Method A in ASTM D412-98a (Reapproved 2002) as described above.
[0033] Polishing layer materials that exhibit high elongation at break values tend to deform reversibly when subjected to machining operations, resulting in unacceptably poor groove formation and inadequate texture generation during diamond conditioning. The unique curing system used in the formation of the polishing layer of the chemical mechanical polishing pad of the present invention provides both a Shore D hardness of 40 to 70, 45 to 55, or 50 to 55 and an elongation at break of 125% to 300%, 140% to 300%, 150% to 250%, or 150% to 200% as measured according to Test Method A in ASTM D412-98a (Reapproved 2002) as described above.
[0034] The polishing layer can have an average thickness of 20 to 150 mils, 30 to 125 mils, 40 to 120 mils, or 50 to 100 mils (0.5 to 3.8 mm, 0.8 to 3.2 mm, 1.0 to 3.0 mm, or 1.3 to 2.5 mm).
[0035] The chemical mechanical polishing pad of the present invention can be adapted to engage with a platen of a polishing machine. For example, the chemical mechanical polishing pad can be adapted to be fixed to a platen of a polishing machine. For example, at least one of a pressure sensitive adhesive and a vacuum can be used for fixing.
[0036] The chemical mechanical polishing pad of the present invention may optionally further include at least one additional layer interfacing with the polishing layer. For example, the chemical mechanical polishing pad may optionally further include a compressible base layer adhered to the polishing layer. The compressible base layer may improve the conformability of the polishing layer to the surface of the substrate being polished.
[0037] An important step in a substrate polishing operation is determining the endpoint of the process. A common in-situ method for endpoint detection involves providing a polishing pad having one or more windows that are transparent to light of a selected wavelength. During polishing, a light beam is directed through the window to the substrate surface, where it reflects and passes through the window back to a detector (e.g., a spectrophotometer). Based on the returned signal, the characteristics of the substrate surface (e.g., the thickness of the film thereon) can be determined for endpoint detection purposes. To facilitate such light-based endpoint methods, the chemical mechanical polishing pad of the present invention optionally further includes an endpoint detection window. The endpoint detection window can be selected from an integrated window incorporated into the polishing layer; and an inserted endpoint detection window block incorporated into the chemical mechanical polishing pad. One of ordinary skill in the art will know to select appropriate construction materials for the endpoint detection window used in the intended polishing method. Method of making a mat
[0038] The method of making the chemical mechanical polishing pad of the present invention may include combining an isocyanate-terminated urethane prepolymer and a curing system to form a combination; reacting the combination to form a product; forming a polishing layer from the product; and forming a chemical mechanical polishing pad having a polishing layer. The combination of the isocyanate-terminated urethane prepolymer and the curing system may further include microelements, such as expandable polymer microspheres.
[0039] The method may include providing a mold; pouring the combination into the mold; and reacting the combination in the mold in a heated oven to form a solidified cake; wherein the polishing layer is derived from the solidified cake. For example, the solidified cake is cut (sliced or cut) to derive multiple polishing layers from a single solidified cake. Optionally, the method further includes heating the solidified cake to facilitate the cutting operation. Optionally, the solidified cake can be heated using an infrared heating lamp during the cutting operation, wherein the solidified cake is cut into multiple polishing layers.
[0040] The method of making the chemical mechanical polishing pad of the present invention may optionally further include: providing at least one additional layer (e.g., a base layer or a subpad layer); and bonding the at least one additional layer to the polishing layer to form a chemical mechanical polishing pad. The at least one additional layer may be fixed to the polishing layer by known techniques, such as by using an adhesive (e.g., a pressure sensitive adhesive, a hot melt adhesive, a contact adhesive).
[0041] The method of making the chemical mechanical polishing pad of the present invention optionally further comprises: providing an endpoint detection window; and incorporating the endpoint detection window into the chemical mechanical polishing pad. Polishing method
[0042] The method of the present invention for chemical mechanical polishing a substrate preferably comprises: providing a chemical mechanical polishing apparatus having a platen; providing at least one substrate to be polished (e.g., wherein the substrate is selected from the group consisting of at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate; preferably, wherein the substrate is a semiconductor substrate); providing a chemical mechanical polishing pad of the present invention; mounting the chemical mechanical polishing pad on the platen; optionally, providing a polishing medium (e.g., a polishing slurry containing a reactive liquid formulation or a non-abrasive) at an interface between the polishing surface of the chemical mechanical polishing pad and the substrate; creating a dynamic contact between the polishing surface and the substrate, wherein at least some material is removed from the substrate; and optionally, conditioning the polishing surface with an abrasive conditioner. The polishing slurry may comprise, for example, a cerium oxide abrasive with or without a chemical additive. Optionally, in the method of the present invention, the provided chemical mechanical polishing apparatus further comprises a light source and a light sensor (preferably a multi-sensor spectrometer); and the provided chemical mechanical polishing pad further comprises an endpoint detection window; and the method further comprises: determining a polishing endpoint by transmitting light from the light source through the endpoint detection window and analyzing light reflected from the substrate surface back through the endpoint detection window and incident on the photosensor. Examples Forming a polishing layer
[0043] The isocyanate-terminated urethane prepolymer was mixed with a curing system and expandable polymer microspheres according to the formulations shown in Table 1. For each formulation, the isocyanate-terminated urethane prepolymer had an NCO% of about 9.1%. The sulfur-containing curing agent marked as SC1 included 95-98 weight percent of dimethylthiotoluenediamine and 2-3 weight percent of monomethylthiotoluenediamine. The high molecular weight polyol curing agent marked as HMWC2 had an average molecular weight of about 11,400 g / mol and a nominal functionality of OH groups of 6. The expandable polymer microspheres were added to the mixture in an amount to obtain a specific gravity as described in Table 1. The amounts of the isocyanate-terminated urethane prepolymer and the curing system were selected to provide a stoichiometric ratio of reactive hydrogen groups in the curing system to unreacted NCO groups in the isocyanate-terminated urethane prepolymer as shown in the table. The mixture was fed to a mold and heated to form a cured composition. The density or specific gravity was determined by the actual weight and volume of the cutting pad using the polymer density. The cured composition is formed into a thickness useful as a polishing layer and applied to a subpad. Table 1 The pads having the polishing layer were tested for defects.
[0044] The pads were fabricated with polishing layers having the formulations listed in Table 1. These pads were used to polish 3 sets of wafers with ceria slurry.
[0045] The first set of wafers were polished with a pad having a polishing layer of the formulation listed in Table 2 and the wafers were examined for scratch and chatter mark defects by scanning electron microscopy. The data normalized to the pad containing the formulation of Comparative 1 is found in Table 2, showing significant improvement in defects for the formulation of the present invention.
[0046] A second set of wafers were polished with a pad having a polishing layer of the formulation listed in Table 3, and the wafers were examined by scanning electron microscopy for scratch and chatter mark defects and TEOS and SiN removal. The data normalized to the pad containing the formulation of Comparative 1 is found in Table 3, showing significant improvement in defects and improvement in SiN removal for the formulation of the present invention.
[0047] A third set of wafers were polished with a pad having a polishing layer having the formulation listed in Table 4, and the wafers were examined by scanning electron microscopy for scratch and chatter mark defects and TEOS and SiN removal. The data normalized to the pad containing the formulation of Comparative 1 is found in Table 4, showing significant improvement in defects and improvement in SiN removal for the formulation of the present invention, with little to no reduction in TEOS removal. Table 2 - Test Group 1 Table 3 - Test Group 2 Table 4 - Test Group 3
[0048] Accordingly, the following non-limiting aspects are disclosed herein:
[0049] Aspect 1. A chemical mechanical polishing pad comprising a polishing layer having a polishing surface, wherein the polishing layer comprises a reaction product of an isocyanate-terminated urethane prepolymer and a curing system; and the curing system comprises (a) a sulfur-containing diamine curing agent and (b) a high molecular weight polyol curing agent, wherein the high molecular weight polyol curing agent has a number average molecular weight MN of 2,500 to 100,000; and wherein the high molecular weight polyol curing agent has an average of 3 to 10 hydroxyl groups per molecule; wherein the weight ratio of the high molecular weight polyol curing agent to the sulfur-containing diamine curing agent is in the range of 3:10 to 7:10.
[0050] Aspect 2. The chemical mechanical polishing pad of aspect 1, wherein the sulfur-containing diamine curing agent comprises a diamine-functional aromatic compound having one or more alkylthio groups pendant to an aromatic ring.
[0051] Aspect 3. The chemical mechanical polishing pad of aspect 1 or 2, wherein the sulfur-containing diamine curing agent comprises dialkylthiotoluenediamine, monoalkylthiotoluenediamine, or both, in each case wherein the alkyl group contains 1, 2, or 3 carbon atoms.
[0052] Aspect 4. The chemical mechanical polishing pad of any of the previous aspects, wherein the sulfur-containing diamine curing agent comprises at least 95 weight percent of dimethylthiotoluenediamine based on the total weight of the diamine curing agent.
[0053] Aspect 5. The chemical mechanical polishing pad of any of the previous aspects, wherein the weight ratio of the high molecular weight polyol curing agent to the sulfur-containing diamine is in the range of 4:10 to 5:10.
[0054] Aspect 6. The chemical mechanical polishing pad of any of the previous aspects, wherein the isocyanate terminated urethane prepolymer has 8.3 to 9.8 wt % of unreacted NCO groups.
[0055] Aspect 7. The chemical mechanical polishing pad of any of the previous aspects, wherein the cure system has multiple reactive hydrogen groups and the isocyanate-terminated urethane prepolymer has multiple unreacted NCO groups; and, wherein the stoichiometric ratio of the reactive hydrogen groups to the unreacted NCO groups is 0.85 to 1.15.
[0056] Aspect 8. The chemical mechanical polishing pad of any of the previous aspects, wherein the polishing layer has a density of 0.7 to 1.1 g / cm3 as determined by dividing its actual weight by its actual volume.
[0057] Aspect 9. The chemical mechanical polishing pad of any of the previous aspects, wherein the polishing layer comprises expanded polymer microspheres.
[0058] Aspect 10. The chemical mechanical polishing pad of any of the previous aspects, wherein the polishing surface comprises grooves in a pattern of concentric circles, radials, or a combination thereof.
[0059] Aspect 11. The chemical mechanical polishing pad of any of the previous aspects, wherein the high molecular weight polyol curing agent has a number average molecular weight of 5,000 to 50,000, preferably 7,500 to 25,000; or more preferably 10,000 to 12,000.
[0060] Aspect 12. The chemical mechanical polishing pad of any of the previous aspects, wherein the high molecular weight polyol curing agent has an average of four to eight, preferably five to seven, or more preferably six hydroxyl groups per molecule.
[0061] All ranges disclosed herein are inclusive of the endpoints, and the endpoints are independently combinable with each other (e.g., the range of "up to 25 wt.%, or more specifically 5 wt.% to 20 wt.%" includes the endpoint and all intermediate values within the range of "5 wt.% to 25 wt.%, etc.). In addition, the upper and lower limits can be combined to form ranges (e.g., "at least 1 or at least 2 weight percent" and "up to 10 or 5 weight percent" can be combined into the ranges "1 to 10 weight percent", or "1 to 5 weight percent", or "2 to 10 weight percent", or "2 to 5 weight percent").
[0062] The present disclosure may alternatively include, consist of or consist essentially of any suitable component disclosed herein. The present disclosure may additionally or alternatively be formulated so as to be free of, or substantially free of, any component, material, ingredient, adjuvant or substance used in prior art compositions or otherwise not necessary to achieve the functions and / or objectives of the present disclosure.
[0063] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term from the present application takes precedence over the conflicting term from the incorporated reference.
[0064] Unless stated to the contrary herein, all test standards are the most current standards in effect as of the filing date of the present application or, if priority is claimed, as of the filing date of the earliest priority application in which the test standards appear.
Claims
1. A chemical mechanical polishing pad comprising a polishing layer having a polishing surface, wherein the polishing layer comprises a reaction product of an isocyanate-terminated urethane prepolymer and a curing system; the curing system comprises (a) a sulfur-containing diamine curing agent, and (b) a high molecular weight polyol curing agent, wherein the high molecular weight polyol curing agent has a number average molecular weight Mn of 2,500 to 100,000; and wherein the high molecular weight polyol curing agent has an average of 3 to 10 hydroxyl groups per molecule; The weight ratio of the high molecular weight polyol curing agent to the sulfur-containing diamine curing agent is in the range of 3:10 to 7:
10.
2. The chemical mechanical polishing pad according to claim 1, wherein The sulfur-containing diamine curing agent includes a diamine-functional aromatic compound having one or more alkylthio groups pendant to an aromatic ring.
3. The chemical mechanical polishing pad according to claim 2, wherein: The sulfur-containing diamine curing agent includes dialkylthiotoluenediamines, monoalkylthiotoluenediamines, or both, in each case wherein the alkyl group contains 1, 2, or 3 carbon atoms.
4. The chemical mechanical polishing pad according to claim 1, wherein: The sulfur-containing diamine curing agent includes at least 95 weight percent of dimethylthiotoluenediamine based on the total weight of the diamine curing agent.
5. The chemical mechanical polishing pad according to claim 1, wherein: The weight ratio of the high molecular weight polyol curing agent to the sulfur-containing diamine is in the range of 4:10 to 5:
10.
6. The chemical mechanical polishing pad according to claim 1, wherein: The isocyanate-terminated urethane prepolymer has 8.3 to 9.8 wt % of unreacted NCO groups.
7. The chemical mechanical polishing pad according to claim 1, wherein: The curing system has a plurality of reactive hydrogen groups, and the isocyanate-terminated urethane prepolymer has a plurality of unreacted NCO groups; and wherein the stoichiometric ratio of the reactive hydrogen groups to the unreacted NCO groups is 0.85 to 1.
15.
8. The chemical mechanical polishing pad according to claim 1, wherein: The polishing layer has a density of 0.7 to 1.1 g / cm3 as determined by dividing its actual weight by its actual volume.
9. The chemical mechanical polishing pad according to claim 1, wherein: The polishing layer comprises expanded polymer microspheres.
10. The chemical mechanical polishing pad according to claim 1, wherein: The polishing surface includes grooves in a pattern of concentric circles, radial directions, or a combination thereof.